The shift of a concept of danger among men and women audience as the impact of news TV-content - ЛавроваЕлена Васильевна; МатвееваЛидия Владимировна (Communications. Media. Design, 2017)
The article describes a study of the impact of news programs on the perception of danger in men and women. It is shown that situational anxiety after watching news programs increases regardless of sex, but cognitive assessment of situations varies in men and women in different ways. For men, after watching the news, dangerous situations of an ordinary type seem less large-scale, less intensive and more controlled, and situations of a catastrophic type, on the contrary, are more probable, more intense and less controlled. In the women’s sample, different situations: both everyday and catastrophic types begin to be perceived as more intense and probable.